Thermally conductive filler, thermally conductive composite material, wire harness, and method for manufacturing thermally conductive filler

By using hollow particles with polar groups coated with a thermally conductive layer, the thermally conductive filler achieves high thermal conductivity and low specific gravity, addressing the challenges of weight reduction and heat dissipation in electronic components.

JP7657873B2Active Publication Date: 2025-04-07AUTONETWORKS TECH LTD +3
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023144154
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-04-07
Estimated Expiration
2039-12-23

AI Technical Summary

Technical Problem

Existing thermally conductive fillers made from inorganic compounds face challenges in achieving high thermal conductivity while maintaining a low specific gravity, which is essential for weight reduction in electrical and electronic components, particularly in automotive applications.

Method used

The development of thermally conductive fillers comprising hollow particles with polar groups on their surfaces, coated with a thermally conductive layer containing an inorganic compound, such as aluminum oxide. This design reduces the specific gravity of the filler while enhancing its thermal conductivity.

Benefits of technology

The proposed filler achieves high thermal conductivity while maintaining a low specific gravity, effectively addressing the weight reduction and heat dissipation requirements in electronic components. The hollow particles reduce the overall specific gravity, while the thermally conductive layer ensures efficient heat transfer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657873000003
    Figure 0007657873000003
  • Figure 0007657873000004
    Figure 0007657873000004
  • Figure 0007657873000001
    Figure 0007657873000001
Patent Text Reader

Abstract

To provide a heat conductive filler which can exhibit high heat conductivity while reducing a specific gravity, a heat conductive composite material and a wire harness including the heat conductive filler, and a method for manufacturing a heat conductive filler which can manufacture the heat conductive filler.SOLUTION: A heat conductive filler 10 has hollow particles 11 having a polar group thereon, and a heat conductive layer 12 which coats the surface of the hollow particles 11 and contains an inorganic compound. A heat conductive composite material 1 includes the heat conductive filler 10 and a matrix material 2, in which the heat conductive filler 10 is dispersed in the matrix material 2. A wire harness includes the heat conductive composite material 1.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a thermally conductive filler, a thermally conductive composite material, a wire harness, and a method for manufacturing the thermally conductive filler. [Background technology]

[0002] In insulating members constituting electric and electronic components, thermally conductive fillers are sometimes added to organic polymer materials for the purpose of increasing heat dissipation and minimizing the effects of heat generation due to electrical current, etc. Thermally conductive fillers are often made of inorganic compounds with high thermal conductivity, such as alumina, aluminum nitride, and boron nitride.

[0003] In recent years, in various electric and electronic components, including automotive electronics, the amount of heat generated during current flow has tended to increase due to the progress of large current and integration. As a means of suppressing the effects of heat generation, for example, in the case of automotive wire harnesses, efforts have been made to improve heat dissipation by improving the shape and structure of components, such as flattening the electric wires to increase their surface area and efficiently contacting the electric wires with highly thermally conductive exterior materials. On the other hand, it is also important to improve heat dissipation by increasing the thermal conductivity of the materials themselves that constitute the insulating members of electric and electronic components, such as electric wire coatings and electric wire exterior materials.

[0004] Mixing a large amount of filler into an organic polymer material or the like can increase the thermal conductivity of the material, but mixing a large amount of filler made of an inorganic compound into an organic polymer material increases the specific gravity of the material, making it difficult to reduce the weight of electric and electronic parts. From the perspective of reducing the weight of the entire automobile, weight reduction is important for electric and electronic parts for automobiles. Therefore, weight reduction is desired for materials containing thermally conductive fillers. As a method for achieving this, attempts have been made to reduce the amount of filler added.

[0005] In order to maintain high thermal conductivity while keeping the amount of filler added low, the shape and particle arrangement of the filler have been devised. For example, Patent Document 1 discloses a filler having voids inside and a porosity within a predetermined range. Patent Document 2 discloses an inorganic-organic composite composition in which boron nitride particles are dispersed in a resin matrix in the form of exfoliated flat particles produced by a peeling process in which secondary particles, which are a laminate of primary particles, are peeled off from each other. Patent Document 3 discloses a highly thermally conductive composite in which highly thermally conductive fillers having anisotropic shapes are in direct contact with each other to form a network structure in the matrix resin. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2019-1849 A [Patent Document 2] JP 2012-255055 A [Patent Document 3] JP 2010-13580 A [Patent Document 4] JP 2012-122057 A [Patent Document 5] JP 2015-178543 A [Patent Document 6] JP 2015-108058 A [Patent Document 7] JP 2003-221453 A Summary of the Invention [Problem to be solved by the invention]

[0007] Inorganic compounds such as alumina, aluminum nitride, and boron nitride exhibit high thermal conductivity, but have a large specific gravity. When they are added as fillers to organic polymer materials to form composite materials, it is difficult to achieve high thermal conductivity while keeping the specific gravity of the composite material as a whole low. In particular, fillers made of oxides such as alumina tend to have a large specific gravity. As described in Patent Documents 1 to 3, the amount of inorganic compounds added can be reduced to a certain extent by devising the shape and particle arrangement of the filler, but there is a limit to this. If the specific gravity of the filler itself can be reduced by considering the constituent materials of the filler, it may be possible to achieve both weight reduction and high thermal conductivity to a higher degree in composite materials to which the filler is added.

[0008] Therefore, the objective of the present invention is to provide a thermally conductive filler that can exhibit high thermal conductivity while keeping the specific gravity low, a thermally conductive composite material and a wire harness that contain such a thermally conductive filler, and a method for producing such a thermally conductive filler. [Means for solving the problem]

[0009] The thermally conductive filler of the present disclosure comprises hollow particles having polar groups on the surfaces thereof, and a thermally conductive layer containing an inorganic compound that coats the surfaces of the hollow particles.

[0010] The thermally conductive composite material of the present disclosure includes the thermally conductive filler and a matrix material, wherein the thermally conductive filler is dispersed in the matrix material.

[0011] The wire harness of the present disclosure includes the thermally conductive composite material.

[0012] The method for producing the thermally conductive filler disclosed herein includes a step of using a raw material that constitutes the thermally conductive layer, either as is or through a chemical reaction, and raw material particles that are configured as hollow particles having polar groups on their surfaces, to bond the raw material to the polar groups on the surfaces of the raw material particles, thereby producing the thermally conductive filler. Effect of the Invention

[0013] The thermally conductive filler according to the present disclosure is a thermally conductive filler that can exhibit high thermal conductivity while keeping the specific gravity low. The thermally conductive composite material and wire harness according to the present disclosure contain such a thermally conductive filler. The method for producing the thermally conductive filler according to the present disclosure can produce such a thermally conductive filler. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a schematic diagram illustrating the configuration of a thermally conductive filler and a thermally conductive composite material according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is a side view showing the wire harness according to the embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] [Description of the embodiments of the present disclosure] First, embodiments of the present disclosure will be listed and described.

[0016] The thermally conductive filler according to the present disclosure comprises hollow particles having polar groups on the surfaces thereof, and a thermally conductive layer containing an inorganic compound that coats the surfaces of the hollow particles.

[0017] The thermally conductive filler includes hollow particles as a constituent material, and has a thermally conductive layer containing an inorganic compound on the surface of the hollow particles. The hollow particles have a cavity inside, and therefore exhibit a low specific gravity as a whole. Therefore, by using hollow particles to form a filler, the specific gravity of the thermally conductive filler as a whole is smaller than when the thermally conductive filler is made of only inorganic compounds. On the other hand, in the thermally conductive filler particles, the thermally conductive layer containing an inorganic compound covers the surface of the hollow particles, so that the filler particles come into contact with other filler particles or other materials surrounding the periphery in the thermally conductive layer. Therefore, even if the hollow particles themselves do not have high thermal conductivity, the thermally conductive layer covering the surface allows the filler particles as a whole to exhibit high thermal conductivity. In this way, it is possible to ensure high thermal conductivity while keeping the specific gravity low in the thermally conductive filler.

[0018] By having polar groups on the surface of the hollow particles, the inorganic compound constituting the thermally conductive layer or the raw material for the inorganic compound can be easily bonded to the surface of the hollow particles through interaction or chemical reaction with the polar groups. As a result, a thermally conductive filler in which the surface of the hollow particles is coated with a thermally conductive layer can be stably and easily formed.

[0019] Here, the polar group is preferably an acidic group. Since the acidic group is negatively charged, it stably forms an ionic bond with the inorganic compound or its raw material, which is in a positively charged state. Therefore, a thermally conductive layer containing an inorganic compound can be stably and easily formed on the surface of the hollow particles.

[0020] The polar group may be bonded to the surface of the hollow particle via a siloxane bond. When the hollow particle has silicon atoms on its surface, the siloxane bond can be easily formed on the surface of the hollow particle using a silane coupling agent. By using a silane coupling agent that contains a polar group such as an acidic group or a functional group that can form a bond with a compound that has a polar group, various polar groups can be stably introduced onto the surface of the hollow particle.

[0021] The hollow particles may be formed as hollow bodies made of a material containing an inorganic compound different from that of the thermally conductive layer, or a material containing an organic polymer, so that a thermally conductive filler having a low specific gravity and excellent thermal conductivity can be formed by using hollow particles made of various materials.

[0022] The hollow particles may be formed as hollow glass bodies whose surfaces have been treated with polar groups. Various polar groups can be easily introduced to the surfaces of the glass particles using a silane coupling agent. In addition, hollow glass particles with controlled particle size and shape can be obtained relatively easily and inexpensively.

[0023] The thermally conductive layer may contain a compound containing at least one of Al and Mg. Compounds of Al and Mg, including oxides, exhibit high thermal conductivity. In addition, raw material compounds of Al and Mg, including alkoxides and carbonates, that can be bonded to the surface of hollow particles to form a stable compound film, are easily available. Therefore, by forming the thermally conductive layer as a compound containing Al and Mg, a thermally conductive filler that has both low specific gravity and high thermal conductivity can be easily manufactured.

[0024] The thermally conductive filler preferably has a specific gravity of 1.5 or less, whereby the low specific gravity of the thermally conductive filler can be sufficiently ensured.

[0025] The thermally conductive composite material according to the present disclosure includes the thermally conductive filler and a matrix material, in which the thermally conductive filler is dispersed in the matrix material.

[0026] The thermally conductive composite material contains the thermally conductive filler having hollow particles and a thermally conductive layer covering the surfaces of the hollow particles, as described above, and can therefore improve heat dissipation by utilizing the high thermal conductivity of the thermally conductive filler while keeping the specific gravity of the thermally conductive composite material low as a whole.

[0027] Here, the matrix material may contain an organic polymer. Many organic polymers have low thermal conductivity, but by mixing the thermally conductive filler having a thermally conductive layer on the surface, high heat dissipation can be ensured for the thermally conductive composite material as a whole. On the other hand, many organic polymers have a relatively low specific gravity, but the specific gravity of the thermally conductive composite material can be kept low even with the thermally conductive filler added, by mixing the thermally conductive filler containing hollow particles and having a low specific gravity.

[0028] The thermally conductive composite material preferably has a specific gravity of 1.5 or less, in which case the specific gravity of the thermally conductive composite material as a whole is kept sufficiently small.

[0029] The thermally conductive composite material preferably has a thermal conductivity of 0.9 W / (m·K) or more at room temperature, which ensures a sufficiently high thermal conductivity for the entire thermally conductive composite material.

[0030] A wire harness according to the present disclosure includes the thermally conductive composite material.

[0031] Since the wire harness contains the above-described thermally conductive composite material, it is possible to utilize high thermal conductivity while keeping the specific gravity of the constituent members small. Therefore, high heat dissipation can be obtained while keeping the mass of the wire harness small as a whole. Therefore, even if heat is generated due to the passage of electricity through the electric wires constituting the wire harness, the influence of the heat can be kept small while maintaining the light weight of the wire harness.

[0032] The method for producing a thermally conductive filler according to the present disclosure includes a step of using a raw material constituting the thermally conductive layer, either as is or through a chemical reaction, and raw material particles constituted as hollow particles having polar groups on their surfaces, to bond the raw material to the polar groups on the surfaces of the raw material particles, thereby producing the thermally conductive filler.

[0033] According to the above-mentioned manufacturing method, a thermally conductive filler having a low specific gravity and high thermal conductivity can be easily manufactured by forming a thermally conductive layer containing an inorganic compound on the surface of raw material particles configured as hollow particles. By using raw material particles having polar groups on the surface, the raw material substance that becomes the thermally conductive layer can be stably and easily bonded to the surface of the raw material particles via the polar groups.

[0034] Here, the raw material may be at least one of a metal alkoxide and a metal carbonate, and then a thermally conductive layer containing a metal oxide can be formed on the surface of the raw material particles through a simple chemical reaction process, thereby obtaining a thermally conductive filler.

[0035] [Details of the embodiment of the present disclosure] The thermally conductive filler, the thermally conductive composite material, the wire harness, and the manufacturing method of the thermally conductive filler according to the embodiments of the present disclosure will be described in detail below with reference to the drawings. The thermally conductive filler according to the embodiments of the present disclosure is included to constitute the thermally conductive composite material according to the embodiments of the present disclosure. Also, the wire harness according to the embodiments of the present disclosure is included to constitute the thermally conductive composite material according to the embodiments of the present disclosure. Furthermore, the manufacturing method according to the embodiments of the present disclosure can manufacture the thermally conductive filler according to the embodiments of the present disclosure.

[0036] In this specification, various physical properties are measured at room temperature in the atmosphere unless otherwise specified. In addition, in this specification, when a certain component is the main component of a certain material, it means that the component accounts for 50% by mass or more of the mass of all the components constituting the material.

[0037] <Thermal conductive filler> First, a thermally conductive filler according to one embodiment of the present disclosure (hereinafter, may be simply referred to as "filler") will be described.

[0038] (Overall composition) 1, a thermally conductive filler 10 according to an embodiment of the present disclosure has hollow particles 11 and a thermally conductive layer 12, and is in the form of particles. The thermally conductive layer 12 covers the surface of the hollow particles 11.

[0039] The hollow particles 11 are particles having a cavity 11a inside the particle. The cavity 11a is occupied by a gas, typically air, except for solid or liquid components that are inevitably incorporated during the manufacturing process of the hollow particles 11 or the filler 10. The specific constituent materials of the hollow particles 11 and the thermally conductive layer 12 will be described later, but the hollow particles 11 are made of a material different from that of the thermally conductive layer 12, and have polar groups, i.e., functional groups having polarity, on their surfaces (outer surfaces). On the other hand, the thermally conductive layer 12 is formed as a layer containing an inorganic compound.

[0040] Since the hollow particles 11 have cavities 11a filled with a gas such as air, the particles as a whole have a low specific gravity and low thermal conductivity compared to solid particles that have no cavities and are entirely occupied by solid materials. Therefore, the hollow particles 11 have a lower specific gravity and lower thermal conductivity than the thermally conductive layer 12 formed as a layer of an inorganic compound. In the thermally conductive filler 10 according to this embodiment in which the thermally conductive layer 12 is provided on the surface of the hollow particles 11, the hollow particles 11 having a low specific gravity are contained, so that the overall specific gravity can be made smaller than that of conventional general fillers entirely made of inorganic compounds.

[0041] On the other hand, the thermally conductive layer 12 covering the surface of the hollow particle 11 can have high thermal conductivity by containing an inorganic compound, and can increase the thermal conductivity of the filler 10 as a whole. As shown in FIG. 1, the thermally conductive layer 12 on the surface of the filler particle 10 contacts the matrix material 2 surrounding the filler particle 10 or the thermally conductive layer 12 on the surface of other filler particles 10, thereby contributing to thermal conduction between the filler particle 10 and the matrix material 2, and between the filler particles 10. Since the thermally conductive layer 12 is provided only on the surface of the hollow particle 11, the volume of the filler particle 10 as a whole is secured by the hollow particle 11, and the thermal conductivity can be exhibited by the thermally conductive layer 12 having a small volume. Adjacent filler particles 10 can contact each other via the thermally conductive layer 12 on the surface layer to form a thermal conduction path.

[0042] From the viewpoint of avoiding an increase in the mass of the filler 10, the specific gravity of the filler 10 as a whole is preferably 1.5 or less, more preferably 1.2 or less, or 1.0 or less. On the other hand, from the viewpoint of avoiding the inability to form the thermally conductive layer 12 with a sufficient thickness due to the specific gravity being suppressed too small, the specific gravity of the filler 10 as a whole is preferably 0.3 or more, more preferably 0.5 or more. The specific gravity of the filler 10 can be measured as the true density of the powdered filler 10, for example, using a specific gravity meter. The specific gravity of the filler 10 as a whole is used as the specific gravity R2 in the formula (1) that will be described later for the proportion of the thermally conductive layer 12. Next, the configurations of the hollow particles 11 and the thermally conductive layer 12 will be described in detail.

[0043] (hollow particles) As described above, hollow particle 11 is a granular body having cavity 11a. Here, cavity 11a is a space that is entirely surrounded by shell 11b made of the solid material that constitutes hollow particle 11 and is isolated from the environment outside hollow particle 11. Hollow particle 11 does not have a pore structure that communicates with the outside environment, such as that present in a porous body, except for those that are inevitably formed.

[0044] The material constituting the hollow particles 11 (the shells 11b) is not particularly limited, and may be an organic substance or an inorganic substance different from the inorganic compound constituting the thermally conductive layer 12. Examples of the organic substance include various resins, elastomers, rubber, and other organic polymers (including polymers as well as those with a low degree of polymerization such as oligomers). Examples of the inorganic substance include metals or inorganic compounds such as glass and ceramics. The hollow particles 11 may be made of only one type of material, or may be made of two or more types of materials in combination by mixing or laminating. The hollow particles 11 may be made of a composite material of an organic material and an inorganic material.

[0045] A preferred example of the material for the hollow particles 11 is glass. Glass, as a material itself, has a relatively low specific gravity among various inorganic compounds and has a high thermal conductivity compared to organic polymers, etc., so that by using glass as a material for the hollow particles 11 constituting the thermally conductive filler 10, it is highly effective in lowering the specific gravity and increasing the thermal conductivity of the thermally conductive filler 10. In addition, a technology for producing hollow particles using glass and further controlling the particle size and shape has already been established, and glass hollow particles can be obtained at a low cost compared to other types of hollow particles. The type of glass constituting the hollow particles 11 is not particularly limited, and various types of glass such as soda lime glass, silica glass, borate glass, borosilicate glass, lead glass, and phosphate glass can be used. Among these types of glass, it is preferable to use those containing silicon atoms capable of forming siloxane bonds with a silane coupling agent in the structure, such as soda lime glass, silica glass, and borosilicate glass, so that a polar group can be introduced using a silane coupling agent, as described later.

[0046] The hollow particles 11 have polar groups on their surfaces. As described later, the presence of polar groups on the surfaces of the hollow particles 11 allows a bond to be formed between the polar groups of the raw material particles and the raw material to form a stable heat conductive layer 12 when the raw material to form the heat conductive layer 12 is bonded to the surface of the raw material particles to form the hollow particles 11, and this is because a bond can be formed between the polar groups of the raw material particles and the raw material to form the heat conductive layer 12, as described later. The entire shell 11a of the hollow particles 11 may contain a compound having a polar group as a constituent material, or the hollow particles 11 may be made of a material that does not substantially contain polar groups or contains only a small amount of polar groups, and polar groups may be introduced only to the surface (and its vicinity) by surface treatment or the like. Note that the polar groups present on the surfaces of the raw material particles may change in structure or may lose or lose polarity after the formation of the heat conductive layer 12. In these cases, the structure derived from the original polar groups remaining on the surfaces of the hollow particles 11 in the manufactured filler 10 is referred to as the polar group.

[0047] The type of polar group on the surface of the hollow particles 11 (or raw material particles before the thermal conductive layer 12 is formed; hereinafter, the same applies to the description of the polar groups on the surface) is not particularly limited, and may be ionic or nonionic. Examples of ionic polar groups include acidic groups such as carboxyl groups, silanol groups, sulfonic acid groups, phosphoric acid groups, and phenolic hydroxyl groups, and basic groups such as amino groups. Examples of nonionic or weakly ionic polar groups include alcoholic hydroxyl groups, isocyanate groups, epoxy groups, and alkoxysilyl groups. From the viewpoint of forming an ionic bond with the raw material and stably bonding the raw material to the surface of the raw material particles when forming the thermal conductive layer 12, it is preferable that the hollow particles 11 have an ionic polar group on the surface.

[0048] The polar group may have either a positive polarity or a negative polarity. However, the raw material used in forming the thermally conductive layer 12 is often positively charged, such as a metal compound, and from the viewpoint of electrostatically and firmly binding the raw material to the surface of the hollow particle 11, it is preferable that the polar group on the surface of the hollow particle 11 has a negative polarization in a direction away from the surface of the hollow particle 11, as represented by various acidic groups. A bipolar compound such as an amino acid may be bound to the surface of the hollow particle 11 to form the polar group. A form in which an acidic group, which is an ionic polar group having a negative polarization, is present on the surface of the hollow particle 11 is particularly preferable. Furthermore, from the viewpoint of preventing the hollow particles 11 from agglomerating together through the polar group, it is preferable that the polar group does not have a strong hydrogen bond property or a reactivity with surrounding substances. Many acidic groups such as a carboxyl group do not show a strong hydrogen bond property or a reactivity with surrounding substances such as solvent molecules, and such an acidic group can be suitably adopted as the polar group.

[0049] The polar group may be directly bonded to the skeleton structure of the hollow particle 11 or may be bonded via another bond. By using another bond, various polar groups can be introduced to the surface of the hollow particle 11. For example, when the hollow particle 11 is made of glass containing silicon atoms in the skeleton structure, the polar group can be introduced to the surface of the hollow particle 11 via a siloxane bond (-Si-O-Si-). As will be described later, the polar group can be introduced easily via a siloxane bond by surface treatment using a silane coupling agent. In addition to the siloxane bond, the polar group may be bonded to the surface of the hollow particle 11 via another bond. For example, if a silane coupling agent having an isocyanate group is bonded to the surface of the hollow particle 11 via a siloxane bond and then the isocyanate group is reacted with an amino group of an amino acid, a structure in which a carboxyl group is bonded to the surface of the hollow particle 11 via a urea bond in addition to the siloxane bond can be formed.

[0050] From the viewpoint of ease of introduction of polar groups to the surfaces of hollow particles 11, when hollow particles 11 are made of an inorganic substance such as glass, it is preferable to introduce polar groups to the surface portion by surface treatment such as treatment using the above-mentioned silane coupling agent. On the other hand, when hollow particles 11 are made of an organic substance, it is preferable that the organic substance constituting hollow particles 11 itself has a polar group, and the polar group is exposed on the surface of hollow particles 11. Examples of organic polymers having polar groups include (co)polymers containing acrylic acid in the main chain, and acid-modified polymers.

[0051] The hollow particles 11 are not particularly limited in terms of their specific shape and particle size, so long as they have a cavity 11a inside. However, a highly isotropic shape, such as one that can be approximated to a sphere, is preferable in terms of making it easier to form the thermally conductive layer 12 on the surface and increasing the affinity with the matrix material 2. The particle size (median diameter D50; the same applies below) of the hollow particles 11 is preferably 1 μm or more, and more preferably 5 μm or more, from the viewpoint of keeping the specific gravity of the filler 10 as a whole low. On the other hand, from the viewpoint of keeping the influence of the filler 10 on the characteristics of the matrix material 2 to which it is added low and increasing the specific surface area, the particle size of the hollow particles 11 is preferably 100 μm or less, and more preferably 60 μm or less.

[0052] From the viewpoint of keeping the specific gravity of the filler 10 small as a whole, it is preferable that the specific gravity of the hollow particle 11 itself is small. The specific gravity of the hollow particle 11 is not particularly limited as long as the specific gravity of the hollow particle 11 as a whole is smaller than the specific gravity of the thermally conductive layer 12, but the specific gravity (true density) of the hollow particle 11 as a whole including the cavity 11a is, for example, 1.0 or less, preferably 0.5 or less, and further 0.3 or less. There is no particular lower limit for the specific gravity of the hollow particle 11, but the specific gravity of the hollow particle 11 made of an inorganic material such as glass or an organic polymer is generally 0.1 or more. The specific gravity of the hollow particle 11 as a whole including the cavity 11a may be sufficiently small, but the specific gravity of the material itself constituting the shell 11b of the hollow particle 11 is also preferably small, for example, less than the specific gravity of the thermally conductive layer 12, and further less than half the specific gravity of the thermally conductive layer 12.

[0053] (Thermal Conduction Layer) As described above, the thermally conductive layer 12 is configured as a layer containing an inorganic compound (excluding alloys). Preferably, the thermally conductive layer 12 contains an inorganic compound as a main component. The type of inorganic compound is not particularly limited, but a substance exhibiting a higher thermal conductivity than the hollow particles 11, that is, a substance that has a greater effect of improving the thermal conductivity when mixed with the matrix material 2 when the thermally conductive layer 12 is formed on the surface of the hollow particles 11 than when the thermally conductive layer 12 is formed only on the hollow particles 11, is used. In addition, it is preferable that the inorganic compound constituting the thermally conductive layer 12 has a higher thermal conductivity than the matrix material 2 and further has a higher thermal conductivity than the material constituting the shell 11b of the hollow particles 11. From the viewpoint of easily forming a stable thermally conductive layer 12 having high thermal conductivity on the surface of the hollow particles 11, it is preferable that the thermally conductive layer 12 contains a metal compound containing a metal element and a nonmetal element as the inorganic compound. Here, the metal element constituting the metal compound includes semimetals such as B and Si (hereinafter the same).

[0054] Examples of the metal compound constituting the thermally conductive layer 12 include oxides, nitrides, carbides, oxynitrides, carbonitrides, carbonates, hydroxides, borides, etc. containing metal elements, as well as metal silicates, aluminates, titanates, etc. From the viewpoint of excellent thermal conductivity and ease of forming a film-like thermally conductive layer 12 stably on the surface of the hollow particles 11, it is preferable that the thermally conductive layer 12 contains a metal oxide among various metal compounds. It is particularly preferable that the thermally conductive layer 12 is mainly composed of a metal oxide. Since metal oxides tend to have a larger specific gravity than metal nitrides and metal carbides, by forming the thermally conductive layer 12 coexisting with the hollow particles 11 in the filler 10, the effect of reducing the specific gravity by the hollow particles 11 can be greatly enjoyed.

[0055] The inorganic compound constituting the thermally conductive layer 12 preferably contains a compound containing at least one of Al and Mg among various metal compounds. It is particularly preferable that the inorganic compound contains Al. Furthermore, it is preferable that Al and Mg form oxides. This is because Al and Mg compounds, including oxides, exhibit high thermal conductivity and can be easily formed as a film-like thermally conductive layer 12 that is stably and firmly attached to the surface of the particulate hollow particles 11 using commercially available raw material compounds.

[0056] The thermally conductive layer 12 may be made of one or more inorganic compounds. When a plurality of inorganic compounds are used, the inorganic compounds may be mixed, may form a complex, or may be laminated in layers. Furthermore, the thermally conductive layer 12 may contain not only inorganic compounds but also organic substances such as various additives and reaction residues. When the matrix material 2 contains an organic polymer, an organic film may be provided on the surface of the thermally conductive layer 12 from the viewpoint of increasing the affinity with the matrix material 2. However, it is preferable not to provide such an organic film between adjacent filler particles 10 from the viewpoint of increasing the thermal conductivity by direct contact between the thermally conductive layers 12. The thermally conductive layer 12 may cover at least a portion of the surface of the hollow particle 11. From the viewpoint of ensuring sufficient contact via the thermally conductive layer 12 between the filler particle 10 and the matrix material 2, and between adjacent filler particles 10, it is preferable that the thermally conductive layer 12 cover at least half or more of the surface area of ​​the hollow particle 11, or even the entire surface area of ​​the hollow particle 11, except for unavoidable defects, etc.

[0057] The proportion of the heat conductive layer 12 in the filler 10 is not particularly limited, but it is preferable that the heat conductive layer specific gravity ratio R defined by the following formula (1) is 100% or more. R = (R2 - R1) / R1 (1) Here, R1 refers to the specific gravity of only the hollow particles 11, and R2 refers to the specific gravity of the filler 10 as a whole. The larger the thermally conductive layer specific gravity ratio R, the greater the proportion of the area of ​​the filler 10 that is occupied by the thermally conductive layer 12. Note that since the state of the hollow particles 11 is hardly changed by the formation of the thermally conductive layer 12, the specific gravity R1 of the hollow particles 11 can be substituted by the specific gravity of the raw material particles used in producing the filler 10.

[0058] If the thermally conductive layer specific gravity R is 100% or more, the filler 10 has a thermally conductive layer 12 with a sufficient volume, and therefore the thermal conductivity of the filler 10 as a whole is easily increased sufficiently. The thermally conductive layer specific gravity R is preferably 150% or more, and more preferably 300% or more. Furthermore, the thermally conductive layer 12 preferably occupies 5% or more by volume, more preferably 10% or more, or even 20% or more by volume, of the entire filler particle 10. The thickness of the thermally conductive layer 12 is preferably 1% or more, more preferably 3% or more, or even 5% or more of the particle diameter of the filler particle 10 on average.

[0059] On the other hand, if the ratio of the thermally conductive layer 12 in the filler particle 10 is too large, the effect of improving the thermal conductivity of the filler 10 becomes saturated, and the effect of suppressing the specific gravity of the filler particle 10 by containing the hollow particles 11 becomes small. From the viewpoint of avoiding these phenomena, it is preferable to set the specific gravity ratio R of the thermally conductive layer to 500% or less. In addition, it is preferable to set the amount of the thermally conductive layer 12 to the entire filler particle 10 to 40% by volume or less in volume ratio, and 15% or less of the particle diameter of the filler particle 10 in thickness. In addition, since the region of the filler particle 10 occupied by the thermally conductive layer 12 is thinner than the particle diameter of the hollow particles 11, the particle diameter of the filler particle 10 as a whole is not significantly different from the particle diameter of the hollow particles 11, and is preferably 1 μm or more, further 5 μm or more, and 100 μm or less, and further 60 μm or less.

[0060] As described above, the thermally conductive filler 10 according to this embodiment has a double structure in which the thermally conductive layer 12 is formed on the surface of the hollow particle 11, and thus has a reduced specific gravity while maintaining high thermal conductivity. Therefore, by combining the thermally conductive filler 10 with other substances to form a composite material, as in the thermally conductive composite material 1 described later, the thermal conductivity of the composite material can be increased without significantly increasing the specific gravity of the composite material as a whole.

[0061] <Method of manufacturing thermally conductive filler> Next, a description will be given of a method for producing a thermally conductive filler according to an embodiment of the present disclosure, which can produce the above-mentioned thermally conductive filler 10. The thermally conductive filler 10 can be produced by carrying out a particle preparation step and a thermally conductive layer formation step.

[0062] In the particle preparation step, hollow raw material particles are prepared to become hollow particles 11 in the produced filler 10. Methods for producing hollow particles have been developed for various organic and inorganic materials, and the raw material particles may be prepared according to these methods. In addition, many hollow particles are commercially available for inorganic compounds such as glass and organic polymers.

[0063] When the raw material particles do not have polar groups on their surfaces, or when the polarity of the surface is not sufficiently high due to low density of polar groups, etc., the raw material particles are subjected to a surface treatment to introduce polar groups onto the surface. The surface treatment may be carried out by bonding a compound having a desired polar group to the surface of the raw material particles by chemical reaction. In this case, another compound may be interposed between the compound having a polar group and the surface of the raw material particles.

[0064] When the raw material particles are made of glass containing silicon atoms, it is preferable to use a silane coupling agent to introduce polar groups to the surface of the raw material particles through siloxane bonds. In general, the silane coupling agent has an alkoxysilyl group, and by bonding to the surface of the raw material particles, the remaining alkoxysilyl group, or the silanol group generated by hydrolysis of the alkoxysilyl group, or the siloxane bond formed by the reaction of adjacent alkoxysilyl groups, functions as a polar group on the surface of the raw material particles. If the silane coupling agent used for surface treatment has a functional group having polarity other than the alkoxysilyl group, the functional group can be introduced as a polar group on the surface of the raw material particles in addition to the alkoxysilyl group.

[0065] If a silane coupling agent having a reactive functional group other than an alkoxysilyl group is used, the silane coupling agent can be bonded to the surface of the raw material particle, and then another compound (other compound) can be bonded through the reactive functional group to introduce a polar group to the surface of the raw material particle. In this case, the other compound to be bonded to the raw material particle via the silane coupling agent can be one having a reactive group that can react with the reactive group of the silane coupling agent to form a bond in addition to the polar group to be introduced to the surface of the raw material particle. Examples of reactive functional groups that can be introduced to the silane coupling agent to bond the other compound include an isocyanate group, an epoxy group, a vinyl group, an amino group, and a mercapto group. For example, when a silane coupling agent having an isocyanate group is used as the silane coupling agent, a compound having an amino group can be used as the other compound to be bonded to the silane coupling agent in addition to the polar group to be introduced to the surface of the raw material particle. In this case, a urea bond is generated between the isocyanate group and the amino group, and the other compound is bonded to the surface of the raw material particle via the silane coupling agent. An example of a compound having an amino group is an amino acid, in which the carboxyl group contained in the amino acid is bonded to the surface of the raw material particle as a polar group via a siloxane bond and a urea bond.

[0066] As described above, in the particle preparation step, raw material particles having polar groups on the surface are prepared. Next, in the thermal conductive layer formation step, the thermal conductive layer 12 is formed on the surface of the raw material particles. In this case, a direct formation method may be used in which the inorganic compound itself that constitutes the thermal conductive layer 12 in the filler 10 to be manufactured is disposed on the surface of the raw material particles as a raw material, or an indirect formation method may be used in which a raw material that becomes an inorganic compound that constitutes the thermal conductive layer 12 by undergoing an appropriate chemical reaction is disposed on the surface of the raw material particles. In either case, since the raw material particles have polar groups on their surfaces, the raw material can be firmly bonded to the raw material particles by electrostatic interaction (ionic bond) via the polar groups or by the formation of bonds involving chemical reactions.

[0067] In the case of the direct formation method, the raw material placed on the surface of the raw material particles becomes the thermally conductive layer 12 as it is. Examples of the direct formation method include deposition and precipitation. On the other hand, in the case of the indirect formation method, the raw material is placed on the surface of the raw material particles, and then a chemical reaction occurs to form the thermally conductive layer 12. Examples of the indirect formation method include a method in which the raw material is bonded to the polar group on the surface of the raw material particles by an interaction such as an electrostatic interaction (ionic bond) or through a chemical reaction, and then the bonded raw material is subjected to a chemical reaction to form the thermally conductive layer 12 of a desired composition. In particular, when the raw material particles have acidic groups on the surface, it is easy to easily and firmly achieve the bonding of the raw material containing a metal.

[0068] In the thermal conductive layer forming process, first, a raw material liquid is prepared in which raw material particles are dispersed in a dispersion medium (solvent) and raw material materials that will become inorganic compounds that will form the thermal conductive layer 12 are also contained. In the raw material liquid, the raw material materials that will become inorganic compounds that will form the thermal conductive layer 12 must be present in a liquid state, and may be in a molten state in addition to a state dissolved in the dispersion medium (solvent). Alternatively, they may be in a finely dispersed state. Below, a form in which raw material particles are dispersed in the raw material liquid and raw material materials that will form the thermal conductive layer 12 are dissolved will be described. In this case, the solvent used to prepare the raw material liquid is not particularly limited as long as it can disperse the raw material particles without dissolving them and without altering the polar groups on the surface, and can dissolve the raw material materials that will form the thermal conductive layer 12. Examples of the solvent include organic solvents such as toluene and tetrahydrofuran (THF), and alcohols such as isobutyl alcohol.

[0069] When preparing the raw material liquid, for example, raw material particles may be added to a solvent and thoroughly stirred to disperse the raw material particles. Next, the raw material to be the thermally conductive layer 12 may be added to the dispersion liquid of the raw material particles and dissolved by stirring or the like. Through this operation, the raw material is bonded to the polar groups on the surface of the raw material particles by interactions such as electrostatic interactions (ionic bonds) or through chemical reactions. When it is necessary to decompose the raw material to make it possible to bond to the polar groups of the raw material particles, or when a bond is formed between the raw material and the polar groups of the raw material particles through a chemical reaction, if heating or addition of a reactant is required for the decomposition or chemical reaction, these operations may be performed in conjunction with stirring as appropriate.

[0070] Once the raw material is bonded to the surface of the raw material particles, a chemical reaction is then caused in the raw material to convert it into the desired inorganic compound that constitutes the thermally conductive layer 12. At this time, an operation according to the type of chemical reaction required may be performed, for example, in addition to stirring, heating, addition of a reactant, contact with gas molecules such as oxygen, etc. If the conversion from the raw material can be completed only by heating or contact with the atmosphere in addition to stirring, the thermally conductive layer 12 can be easily formed, which is preferable.

[0071] In the thermally conductive layer forming step, after the thermally conductive layer 12 is formed on the surface of the hollow particles 11, the product may be isolated by appropriate filtration or the like. Furthermore, the thermally conductive filler 10 can be obtained by removing volatile components by performing heat drying or vacuum drying.

[0072] As the raw material used in the thermally conductive layer forming process, it is preferable to use one that can form metal ions in the dispersion liquid of the raw material particles or on the surface of the raw material particles. The specific type of compound is not particularly limited, and suitable examples of such raw material include metal alkoxides and metal carbonates. When using a metal alkoxide as the raw material, the metal alkoxide may be added to the dispersion liquid of the raw material particles and stirred while heating. The metal alkoxide undergoes hydrolysis to form a metal hydrate accompanied by the generation of alcohol. In particular, when a trace amount of polar groups such as acidic groups are present on the surface of the raw material particles or in the dispersion medium, the rate of formation of metal hydrates increases in the vicinity. The generated metal hydrate forms an electrostatic bond with the polar groups on the surface of the raw material particles having negative polarization, such as acidic groups, and is firmly bonded to the surface of the raw material particles in the form of a film. Thereafter, the reaction solution is appropriately heated and the dispersion medium is dried, whereby the thermally conductive filler 10 having a thermally conductive layer 12 containing at least one of a metal hydroxide and a metal oxide is obtained through oxidation by oxygen in the air. In many cases, oxidation of the thermally conductive layer 12 progresses to a metal oxide state. The type of metal alkoxide is not particularly limited, and examples include methoxide, ethoxide, isopropoxide, and the like. Aluminum isopropoxide and magnesium ethoxide are easy to use in terms of safety and availability.

[0073] When a metal carbonate is used as a raw material, when a basic carbonate is added to a dispersion of raw material particles, a metal hydroxide is formed on the surface of the raw material particles and is firmly bonded to the surface of the raw material particles to form a film. Thereafter, as in the case of the alkoxide, the reaction solution is appropriately heated and the dispersion medium is dried, whereby the thermally conductive filler 10 having a thermally conductive layer 12 containing at least one of a metal hydroxide and a metal oxide is obtained through oxidation by oxygen in the air. In many cases, the oxidation in the thermally conductive layer 12 progresses to the state of a metal oxide.

[0074] <Thermal conductive composite material> Next, a thermally conductive composite material (hereinafter, sometimes simply referred to as a composite material) according to one embodiment of the present disclosure will be described. As shown in Fig. 1, a thermally conductive composite material 1 according to this embodiment contains a thermally conductive filler 10 according to the embodiment of the present disclosure described above and a matrix material 2. The filler 10 is dispersed in the matrix material 2.

[0075] Since the composite material 1 according to the present embodiment contains the thermally conductive filler 10 having the thermally conductive layer 12 on the surface of the hollow particle 11 described above, the composite material 1 as a whole exhibits high thermal conductivity and has excellent heat dissipation properties due to the high thermal conductivity imparted by the thermally conductive layer 12. At the same time, the hollow particles 11 have an effect of lowering the specific gravity of the thermally conductive filler 10, so that the composite material 1 as a whole has a low specific gravity.

[0076] The type of matrix material 2 is not particularly limited, but it is preferable that the matrix material 2 contains an organic polymer, and more preferably, the matrix material 2 is mainly composed of an organic polymer. Specific examples of the organic polymer constituting the matrix material 2 include various resins, thermoplastic elastomers, rubber, and the like. The organic polymer is not limited to a high molecular weight (polymer), and may be one with a low degree of polymerization, such as an oligomer. When a resin material is used as the matrix material 2, it may be a curable resin, a thermoplastic resin, or a plastic that can be dissolved in a solvent, depending on the desired application. Examples of the resins constituting the matrix material 2 include olefin resins such as polyethylene and polypropylene, halogen-based resins such as polyvinyl chloride, polylactic acid, polystyrene resins, polyvinyl acetate, ABS resin, AS resin, acrylic resin, methacrylic resin, polyamide resin, urethane resin, silicone resin, fluororesin, polyvinyl alcohol, polyimide, polyacetal, polycarbonate, modified polyphenylene ether (PPE), polyethylene terephthalate, polybutylene terephthalate, polyphenylene sulfide, and epoxy resin, or copolymers or polymer alloys of these resins. The matrix material 2 may contain only one type of organic polymer, or may contain multiple types of organic polymers. In addition to the organic polymer, the matrix material 2 may contain additives such as flame retardants, fillers, and colorants as appropriate.

[0077] The specific gravity of the matrix material 2 itself is not particularly limited, but is preferably kept at 1.5 or less from the viewpoint of keeping the specific gravity of the composite material 1 to which the filler 10 is added small as a whole. The specific gravity of the matrix material 2 is not particularly limited, but when an organic polymer is used as the matrix material 2, the specific gravity is generally 0.8 or more. The thermal conductivity of the matrix material 2 itself is not particularly limited, but is preferably 0.1 W / (m·K) or more from the viewpoint of ensuring high thermal conductivity as a whole composite material 1 to which the filler 10 is added. The thermal conductivity of the matrix material 2 is not particularly limited, but is preferably 0.6 W / (m·K) or less from the viewpoint of ensuring high thermal conductivity as a whole composite material 1 to which the filler 10 is added. The specific gravity of the matrix material 2 and the composite material 1 can be measured by a water displacement method or the like. The thermal conductivity of these materials can be measured by a laser flash method, a hot wire method, or the like.

[0078] In the composite material 1 according to the present embodiment, the content of the filler 10 may be appropriately determined so that the composite material 1 as a whole has the desired specific gravity and thermal conductivity. Since the thermal conductivity of the composite material 1 increases as the content of the filler 10 increases, the content of the filler 10 may be determined so that the content at which the desired thermal conductivity is obtained is the lower limit. For example, the content of the filler 10 may be determined so that the thermal conductivity of the composite material 1 is 1.5 times or more, further 2 times or more, 3 times or more, or 4 times or more than the thermal conductivity of the matrix material 2 to which the filler 10 is not added. Alternatively, the content of the filler 10 may be determined so that the thermal conductivity of the composite material 1 is 0.6 W / (m·K) or more, further 0.9 W / (m·K) or more, or 1.2 W / (m·K) or more. It is preferable that the thermal conductivity of the composite material 1 is as high as possible. However, in order to avoid an increase in specific gravity due to the excessive addition of the filler 10, it is advisable to keep the thermal conductivity at 50 times or less, or even 30 times or less, the thermal conductivity of the matrix material 2, and at 8.0 W / (m K) or less, or even 5.0 W / (m K) or less.

[0079] The upper limit of the content of the filler 10 in the composite material 1 is not particularly determined, but the content of the filler 10 may be determined so that the specific gravity of the composite material 1 is suppressed to 1.3 times or less, or even 1.2 times or less, of the specific gravity of the matrix material 2 to which the filler 10 is not added. More preferably, the specific gravity of the composite material 1 is equal to or less than the specific gravity of the matrix material 2 to which the filler 10 is not added. Alternatively, the content of the filler 10 may be determined so that the specific gravity of the composite material 1 is suppressed to 1.8 or less, or even 1.5 or less. The smaller the specific gravity of the composite material 1, the more preferable, and no lower limit is particularly determined.

[0080] When the content of the filler 10 is defined as the ratio of the filler 10 to the entire composite material 1, the content of the filler 10 may be set to about 30 volume % or more from the viewpoint of sufficiently improving the thermal conductivity of the composite material 1. On the other hand, the content of the filler 10 may be set to 60 volume % or less from the viewpoint of suppressing an increase in the specific gravity of the composite material 1. In addition, the content of the filler 10 is preferably selected so that the thermal conductive layers 12 of adjacent filler particles 10 come into contact with each other to form a thermal conductive path, as shown in FIG. 1. When the content of the filler 10 in the composite material 1 is defined as the content of the inorganic compound, that is, the ratio of the volume of the inorganic compound forming the thermal conductive layer 12 to the entire composite material 1, the content may be set to 0.5 volume % or more, further 5 volume % or more, and 20 volume % or less.

[0081] As described above, the composite material 1 according to this embodiment has both high thermal conductivity and low specific gravity. Therefore, the composite material 1 can be suitably used as a material for constituting a member that requires both light weight and heat dissipation, such as a wire harness described next. The composite material 1 according to this embodiment can be produced by mixing the powdered filler 10 produced by the production method described above with the matrix material 2 at a predetermined compounding ratio.

[0082] <Wire harness> Finally, a wire harness according to an embodiment of the present disclosure will be described. The wire harness according to this embodiment includes the thermally conductive composite material 1 according to the embodiment of the present disclosure described above. As shown in Fig. 2, the wire harness 5 is provided with a connector 52 including a connection terminal (not shown) at the end of an insulated electric wire 51 having an insulating coating provided on the outer periphery of an electric conductor. In the wire harness 5, a plurality of insulated electric wires 51 may be bundled together, and in this case, a tape 53 can be used as an exterior material for bundling the insulated electric wires 51.

[0083] In the wire harness 5 according to this embodiment, the composite material 1 according to the embodiment of the present disclosure described above can constitute various members that require heat dissipation. In particular, it is preferable to use the composite material 1 in which the filler 10 is added to the organic polymer as the matrix material 2 as an insulating member. Examples of such insulating members include an insulating coating constituting the insulated electric wire 51, an exterior material such as a tape 53 or a protective tube arranged on the outside of the insulated electric wire 51, an adhesive used for bonding or waterproofing between components, and a connector housing constituting the connector 52. The composite material 1 may also be disposed between a protective tube such as a corrugated tube and the insulated electric wire 51.

[0084] In recent years, in the field of automobiles, particularly in electric vehicles and hybrid vehicles, the electric current flowing through the electric wires tends to increase, and the amount of heat generated from the electric wires tends to increase accordingly. In addition, many electric wires and electrical connection members are arranged in close proximity. In these cases, it is important that the various members constituting the wire harness 5 have high heat dissipation properties in terms of minimizing the effect of heat dissipation from the electric wires and electrical connection members. In the wire harness 5, by forming the members that may be affected by such heat dissipation using the composite material 1 having high thermal conductivity, it becomes possible to efficiently dissipate heat. In addition, in the field of automobiles, weight reduction of the constituent members is an important issue, and the use of the composite material 1 having a low specific gravity can also contribute to weight reduction of the wire harness 5. EXAMPLES

[0085] Examples are shown below. The present invention is not limited to these examples. Here, a thermally conductive filler having a thermally conductive layer on the surface of a hollow particle was prepared, and the specific gravity and thermal conductivity were evaluated. Unless otherwise specified, the preparation and evaluation of the sample were performed in air at room temperature.

[0086] [Test Method] (1) Preparation of filler First, a plurality of fillers having a thermally conductive layer on the surface of hollow particles were prepared. In producing the filler, first, in a particle preparation step, the raw material particles were appropriately surface-treated, and then, in a thermally conductive layer formation step, a thermally conductive layer was formed on the surface of the raw material particles.

[0087] (1-1) Particle preparation process The following materials were prepared as the raw materials for making the filler: (Hollow glass particles) G6020: Soda lime borosilicate glass hollow particles (3M "Glass Bubbles K20"); median diameter 60 μm; specific gravity 0.20 G4525: Hollow particles made of borosilicate glass (Potters-Barotini "Sphericel 25P45"); median diameter 45 μm; specific gravity 0.25 G2046 (3M Glass Bubbles iM16K): Soda-lime borosilicate glass hollow particles; median diameter 20 μm; specific gravity 0.46

[0088] (Surface treatment agent) 3-Aminopropyltriethoxysilane (APES) (C2H5O)3Si-C3H6-NH2 Tetraethoxysilane (TEOS) Si(OC2H5)4 ·Vinyltriethoxysilane (VTES) (C2H5O)3Si-CH=CH2 ·3-Isocyanatopropyltriethoxysilane (IPES) (C2H5O)3Si-C3H6-N=C=O DL-Alanine H2N-CH(CH2)-COOH Hexamethyldisilazane (HMDS) (CH3)3Si-NH-Si(CH3)3

[0089] The hollow glass particles were surface-treated using the above-mentioned surface treatment agent to prepare various surface-treated particles as described below. · G60-A: 5g of G6020 and 100mL of acetone were placed in a recovery flask and gently stirred at room temperature to form a suspension. Then, while continuing the suspension, 0.5g of APES was added to the suspension. After stirring at room temperature for 2 hours, a cooling tube was attached, 20mL of pure water was added, and the mixture was stirred at 50°C for 24 hours. It was then filtered, air-dried, and heated in an oven at 140°C for 24 hours. Through the above process, aminopropyltriethoxysilane surface-treated G6020 was obtained as a white powder. G60-T: G6020 surface-treated with tetraethoxysilane was obtained as a white powder in the same manner as in the above-mentioned G60-A, except that TEOS was used instead of APES. G60-V: Vinyltriethoxysilane surface-treated G6020 was obtained as a white powder in the same manner as in the above-mentioned G60-A, except that VTES was used instead of APES. G60-I: The manufacturing method of G60-A was repeated except that IPES was used instead of APES, to obtain isocyanatopropyltriethoxysilane surface-treated G6020 as a white powder. · G60-IA: 5 g of G60-I obtained above and 50 mL of acetone were placed in a recovery flask and gently stirred at room temperature to form a suspension. 10 g of a 2% by mass aqueous solution of DL-alanine was added to the suspension and stirred at 50°C for 24 hours. It was then filtered and air-dried, and further heated in an oven at 140°C for 24 hours. Through the above process, G6020, which had been surface-treated with a carboxylic acid via an isocyanate, was obtained as a white powder. G45-IA: A product was obtained by using G4525 instead of G6020 in the manufacturing method of G60-I described above. This product was used instead of G60-I in the manufacturing method of G60-IA described above to obtain G4520, which was surface-treated with carboxylic acid via isocyanate, as a white powder. G20-IA: A product was obtained by using G2046 instead of G6020 in the manufacturing method of G60-I described above. This product was used instead of G60-I in the manufacturing method of G60-IA described above to obtain G2046, which was surface-treated with carboxylic acid via isocyanate, as a white powder. G60-H: G6020 surface-treated with hexamethyldisilazane was obtained as a white powder in the same manner as in the above-mentioned G60-A, except that HMDS was used instead of APES.

[0090] As described above, various surface-treated particles were prepared. The specific gravity of each of the obtained surface-treated particles was evaluated using an electronic specific gravity meter, and no change in specific gravity was observed before and after the surface treatment. In other words, it was confirmed that the specific gravity was not affected by the above-mentioned surface treatment.

[0091] (1-2) Thermal Conductive Layer Formation Process The various surface-treated particles prepared above and G6020 without surface treatment were used as raw material particles, and a thermally conductive layer containing aluminum oxide was formed on each raw material particle. Specifically, each raw material particle and aluminum isopropoxide (manufactured by Tokyo Chemical Industry Co., Ltd.) were added to isobutyl alcohol, and gently refluxed and stirred at 110°C. The amounts of raw material particles and aluminum isopropoxide added at this time are shown in Table 1 below. For the filler names in Table 1 labeled "F1" after the name of the raw material particle, the amount of aluminum isopropoxide added was adjusted so that the amount of alumina in the filler to be manufactured was 25% by volume in terms of volume ratio and 9% by thickness of the particle diameter of the raw material particle. On the other hand, for the filler names labeled "F2" after the name of the raw material particle, the amount of aluminum isopropoxide added was adjusted so that the amount of alumina in the filler to be manufactured was 10% by volume in terms of volume ratio and 3.5% by thickness of the particle diameter of the raw material particle.

[0092] After heating and stirring at 110°C for 1 hour, 10 mL of pure water was added and the mixture was heated and stirred under reflux for 40 hours. The reaction solution was then returned to room temperature, filtered and air-dried, and the resulting solid component was dried in an oven at 140°C for 48 hours to obtain various fillers.

[0093] Table 1 below summarizes the type, specific gravity, and input amount of raw material particles used as the preparation raw material for each filler, and the input amount of aluminum isopropoxide. Also shown are the specific gravity of the obtained filler and the specific gravity rate of the thermally conductive layer R. Here, the specific gravity of the filler is calculated from the mass ratio of the raw materials, assuming that all aluminum isopropoxide forms alumina. However, in actual fillers, alumina may not only be formed as a thermally conductive layer on the surface of the raw material particles, but may also be formed in other forms, such as alumina particles formed as particles independent of the raw material particles, and the specific gravity calculated here includes all of these forms of alumina. The specific gravity rate of the thermally conductive layer R is calculated by the above formula (1) based on the specific gravity value. It should be noted that the thermally conductive layer formed using aluminum isopropoxide by the above synthesis method has a composition of almost alumina, which has been confirmed by SEM-EDX analysis (energy dispersive X-ray analysis using a scanning electron microscope) for thermally conductive layers similarly formed on the surface of other types of fine particles.

[0094] [Table 1]

[0095] (1-3) Reference sample As reference fillers for comparison with the fillers prepared above, the following were also prepared. Alumina filler: Showa Denko rounded alumina (AS-50) · G6020: The G6020 used above as the raw material for surface treatment was also used as a reference filler.

[0096] (2) Preparation of composite materials The above prepared fillers were dispersed in a matrix material to prepare composite materials for Samples A1 to A10 and Samples B1 to B5. The matrix material constituting the composite materials was a cured product of the following two-liquid epoxy resin. Epoxy base: glycidyl ether of bisphenol A (Mitsubishi Chemical Corporation "jER828"; epoxy equivalent: 190g / eq.) Epoxy hardener: Amine type (Mitsubishi Chemical "ST12"; Amine value: 345~385KOHmg / g)

[0097] Various fillers, epoxy base resin, and epoxy curing agent were mixed in an agate mortar at room temperature in the mass ratios shown in Table 2 below, and degassed for 1 minute under vacuum at room temperature. The mixture was then heated at 100°C for 10 minutes using a heat press molding machine to cure. A portion of the cured body that had no visible bubbles was cut out to prepare a resin cured product test piece (10 mm x 10 mm x 1 mm). For sample B1, no filler was added, and the resin cured product test piece was prepared from epoxy resin alone.

[0098] (3) Characterization of composite materials The specific gravity and thermal conductivity of each of the resin cured test pieces prepared above were measured. The specific gravity was measured by the underwater displacement method. The thermal conductivity was measured by the laser flash method using a thermal conduction device (NETZSCH's "LFA447"). Furthermore, for samples A1 to A5, the cross section of the test piece was observed using a scanning electron microscope (SEM) to evaluate the dispersion state of the filler. As explained above, the produced filler includes not only aluminum compounds such as alumina formed in layers on the surface of the raw material particles, but also particles formed as independent particles from the raw material particles, but the properties evaluated here were all measured for samples in which all components of the aluminum compounds were added as fillers to the matrix material.

[0099] [Test Results] The filler and matrix material compounding ratios (unit: mass%), filler compounding amount (unit: volume%), alumina content (unit: volume%), specific gravity and thermal conductivity measurement results for the composite materials of samples A1 to A10 and samples B1 to B5 are summarized in Table 2. Here, the alumina content is the amount of alumina contained in the entire composite material, and is calculated from the filler compounding amount and the volume ratio of the thermally conductive layer to the filler.

[0100] [Table 2]

[0101] According to Table 2, in samples A1 to A10, in which a heat conductive layer mainly composed of alumina is provided on the surface of hollow particles to which polar groups have been introduced by surface treatment to form a filler, and the filler is then added to a matrix material, despite the addition of 40 volume % of filler, the specific gravity is kept below that of sample B1, which had no added filler.

[0102] In addition, all of the samples A1 to A10 have a thermal conductivity of 0.5 W / (m·K) or more. These values ​​are 1.5 times higher than the thermal conductivity of sample B1, which does not contain any filler. From these results, it can be seen that in samples A1 to A10, which contain fillers with thermally conductive layers formed on the surfaces of hollow particles, the fillers contain hollow particles with low specific gravity, so that the composite material containing the fillers as a whole can obtain high thermal conductivity while keeping the specific gravity low. It is considered that the hollow particles have polar groups on their surfaces, so that a thermally conductive layer can be stably formed on the surfaces of the hollow particles, and a dense thermally conductive layer can cover the surfaces of the hollow particles. Furthermore, due to the effect of the volume occupied by the hollow particles, the thermally conductive layers on the surfaces of adjacent fillers come into contact with each other, forming a thermally conductive path between the filler particles, which is interpreted as being highly effective in improving thermal conductivity.

[0103] Here, we consider samples B2 to B5. In sample B2, hollow glass particles (G6020) themselves are added to the matrix material, and the specific gravity is lower than that of sample B1, which does not contain any filler. However, since it does not contain an inorganic substance that exhibits high thermal conductivity, such as alumina, the thermal conductivity is not improved compared to sample B1, but rather is lower. The thermal conductivity of the glass itself is about 1.0 W / (m·K), which is higher than that of the matrix material, but since it is a hollow particle and air is enclosed, it is interpreted that phonon scattering occurs inside the particle, making it difficult for heat conduction through the particle. Thus, the hollow glass particles themselves cannot be used as a thermally conductive filler.

[0104] Sample B3 is different from Sample B2 in that a thermally conductive layer is formed on the hollow glass particles and then added to the matrix resin. However, although Sample B3 uses the same amount of alumina as Samples A1 to A8, the thermal conductivity is not improved from Sample B1, which does not contain any filler. This indicates that, unlike Samples A1 to A8, the surface treatment for introducing polar groups to the surfaces of the glass particles is not performed, and thus although alumina adheres to the surfaces of the glass particles, the alumina does not function effectively to form a thermal conductive path. It is considered that alumina does not accumulate to cover the surfaces of the glass particles in a continuous layer, but alumina forming small areas is dispersed on the surfaces of the glass particles.

[0105] In sample B4, 10 volume % of alumina filler, which is generally used as a thermally conductive filler, is added. This amount of addition is the same as samples A1 to A8 in terms of alumina content. However, in sample B4, the thermal conductivity is only slightly improved compared to sample B1, which does not contain filler, and is lower compared to samples A1 to A8. This is thought to be because the volume of the filler in the composite material is small, so the contact area between the filler particles is small, and the formation of a thermal conduction path between the filler particles is not effectively achieved.

[0106] In sample B5, alumina filler is added like sample B4, but the amount is 40 volume %. This amount is the same as samples A1 to A8 in terms of the amount of filler (volume ratio of filler). In sample B5, the thermal conductivity is significantly improved compared to sample B1, which does not contain filler. This result is because the amount of alumina filler added is larger than that of sample B4, which increases the contact area between filler particles and forms an effective heat conduction path. However, the volume occupied by alumina itself is larger, so the specific gravity of the composite material is nearly twice that of sample B1. From the evaluation results of samples B4 and B5, it can be said that it is difficult to achieve both low specific gravity and high thermal conductivity when using a filler composed of alumina alone.

[0107] Finally, samples A1 to A10 are compared with each other. First, the types of functional groups introduced to the surfaces of the raw material particles constituting the filler by surface treatment are different in samples A1 to A5 and A8. First, samples A1 to A5 show higher thermal conductivity than sample A8. In samples A1 to A5, a silane coupling agent having an alkoxysilyl group is used as a surface treatment agent, so that molecules having a polar group can be firmly and densely bonded to the surfaces of the glass particles via siloxane bonds, and it is considered that a thermally conductive layer can be formed on the surface with high polarity. On the other hand, in sample A8, the surface treatment agent does not have an alkoxysilyl group and cannot form a siloxane bond with the glass surface, so that the polarity of the glass surface is lower than that of samples A1 to A5, and the generation efficiency of the thermally conductive layer is considered to be lower.

[0108] Among the samples A1 to A5, the thermal conductivity is the lowest in sample A1, the next lowest in sample A3, and the thermal conductivity is significantly higher in samples A2, A4, and A5 than in samples A1 and A3. It is considered that samples A2, A4, and A5 have highly polar groups, such as silanol groups (generated by hydrolysis of alkoxysilyl groups), isocyanate groups, and carboxyl groups, on the surfaces of the hollow particles, respectively, and thus can generate a thermally conductive layer with high efficiency through ionic bonds between the polar groups and metal-containing cations. On the other hand, the surface treatment agent used in sample A3 only has alkoxysilyl groups as functional groups in addition to low-polarity vinyl groups, and sample A1 has amino groups, which are basic groups, introduced into the surface treatment agent in addition to alkoxysilyl groups. In these samples A1 and A3, the formation of the thermally conductive layer proceeds through the electrostatic interaction between the polarized structure of the siloxane bond derived from the alkoxysilyl group or the alkoxysilyl group and the metal-containing cation, but compared to the above-mentioned samples A2, A4, and A5, where the acidity of the functional group is used, the polarity of the surface of the raw material particles is not high, so the generation efficiency of the thermally conductive layer on the surface of the raw material particles is low. The same specific gravity is obtained in samples A1 to A5, and the amount of aluminum compounds contained is the same in each sample, but the amount of aluminum compounds that form a homogeneous layer of thermally conductive layer on the surface of the raw material particles is small in samples A1 and A3, and instead, it is thought that components that form particles independent of the raw material particles or components that form unevenly on the surface of the raw material particles, which do not effectively contribute to improving the thermal conductivity of the composite material, are generated.

[0109] In addition, the cross sections of samples A1 to A5 were observed by SEM to evaluate the dispersibility of the filler particles. As a result, the filler was found to aggregate in samples A1 and A4. On the other hand, sample A5 had particularly excellent dispersibility of the filler. In sample A1, the amino group formed hydrogen bonds, and in sample A4, the isocyanate group remained reactive, which is thought to cause aggregation of the raw material particles in the filler manufacturing process, and this aggregation was inherited in the manufactured filler. In sample A5, the carboxyl group introduced as a polar group does not cause aggregation by forming hydrogen bonds or chemical reactions, so the filler showed high dispersibility, which is also thought to be the reason why the composite material has a particularly high thermal conductivity.

[0110] Samples A5 to A7 differ in the particle size of the raw material particles that make up the filler. However, all of them show the same specific gravity and thermal conductivity. This shows that the particle size of the filler particles does not have a significant effect on the specific gravity and thermal conductivity of the composite material. Therefore, it can be said that the particle size of the composite particles should be appropriately selected taking into consideration the ease of dispersion in the matrix material, the material strength, specific gravity, etc. In this case, the amount of addition should be set according to the particle size of the filler, using the filler blending amount and alumina content in volume percent as indicators.

[0111] Samples A9 and A10 are different from samples A2 and A5 in the amount of the thermally conductive layer formed in the filler. In samples A9 and A10, the thermally conductive layer formed is thinner than samples A2 and A5, so that the specific gravity is lower and the thermal conductivity is also lower. However, even though samples A9 and A10 contain only 4.0% alumina by volume, they show a higher thermal conductivity than sample B4, which contains 10% alumina by volume. This shows that by forming a thermally conductive layer on the surface of the hollow particles and securing the volume of the filler as a whole, even a small amount of the thermally conductive layer can effectively contribute to thermal conduction.

[0112] Although the embodiments of the present disclosure have been described in detail above, the present invention is not limited to the above-described embodiments, and various modifications are possible without departing from the gist of the present invention. [Explanation of symbols]

[0113] 1. (Thermal Conductive) Composite Materials 10 (Thermal Conductive) Filler 11 Hollow particles 11a Cavity 11b Shell 12 Thermal Conductive Layer 2. Matrix material 5. Wire Harness 51 Insulated wire 52 Connector 53 Tape

Claims

1. A method for producing a hollow particle having a polar group on a surface thereof, the hollow particle being surface-treated with a compound having any one of a carboxyl group, a silanol group, a sulfonic acid group, a phosphoric acid group, a phenolic hydroxyl group, an amino group, an alcoholic hydroxyl group, an isocyanate group, an epoxy group, or an alkoxysilyl group; a thermally conductive layer containing an inorganic compound, the thermally conductive layer covering the surface of the hollow particles; the thermally conductive layer is a film-like layer of the inorganic compound attached to a surface of the hollow particles, The thermally conductive layer is a thermally conductive filler containing a metal oxide as the inorganic compound as a main component.

2. The thermally conductive filler according to claim 1 , wherein the polar group is an acidic group.

3. 3. The thermally conductive filler according to claim 1, wherein the polar group is bonded to the surface of the hollow particle via a siloxane bond.

4. The thermally conductive filler according to claim 1 , wherein the hollow particles are formed as hollow bodies made of a material containing an inorganic compound different from that of the thermally conductive layer, or a material containing an organic polymer.

5. The thermally conductive filler according to claim 1 , wherein the hollow particles are configured as hollow bodies of glass that have been surface-treated with a polar group.

6. The thermally conductive filler according to claim 1 , wherein the thermally conductive layer comprises a metal oxide containing at least one of Al and Mg.

7. The thermally conductive filler according to claim 1 , which has a specific gravity of 1.5 or less.

8. A thermally conductive filler according to any one of claims 1 to 7 and a matrix material, A thermally conductive composite material, wherein the thermally conductive filler is dispersed in the matrix material.

9. The thermally conductive composite of claim 8 , wherein the matrix material comprises an organic polymer.

10. 10. The thermally conductive composite material according to claim 8 or 9, having a specific gravity of 1.5 or less.

11. The thermally conductive composite material according to any one of claims 8 to 10, having a thermal conductivity of 0.9 W / (m·K) or more at room temperature.

12. A wire harness comprising the thermally conductive composite material according to any one of claims 8 to 11.

13. A raw material for forming the thermal conductive layer, either as it is or through a chemical reaction, and raw material particles formed as hollow particles having polar groups on the surface are used to form the thermal conductive layer. The raw material is bound to a polar group on the surface of the raw material particle, A method for producing a thermally conductive filler, comprising the steps of: producing the thermally conductive filler according to any one of claims 1 to 7.

14. The method for producing a thermally conductive filler according to claim 13, wherein the raw material is at least one of a metal alkoxide and a metal carbonate.

Citation Information

Patent Citations

  • Thermosetting-resin-based heat-conductive composite material, and preparation method and application thereof

    CN103756252A

  • Conductive composition

    JP2003031028A

  • Inorganic powder carried on board made of polyester fiber

    JP2003221453A

  • Fixing member and heat fixing device

    JP2006017811A

  • High-thermal conductivity composite and method for producing the same

    JP2010013580A